Achieving Sustainable Consumer Protection in the Era of Social Media - Prastyanti, Rina Arum; Prattana Srisuk (Lembaga Contrarius Indonesia, 2025)
The endorsement problem on Instagram is related to the rampant practice of non-transparent influencer marketing, which can mislead consumers and damage public trust in brands. Therefore, there are challenges and opportunities to achieve sustainable consumer protection in the era of social media, especially Instagram. This research explores how existing regulations can be updated to protect consumers more effectively and analyzes the role of influencers in maintaining advertising transparency in realizing Sustainable Consumer Protection. The method used is normative juridical with a conceptual approach, legislation, case studies, and comparative. The research results show that, first the development of technology and social media has influenced how entrepreneurs interact with consumers but also carries the risk of misleading marketing practices. Strengthening the legal framework and more effective law enforcement are needed to protect consumers from losses. In Indonesia, sustainable consumer protection can be achieved by encouraging ethical marketing practices and transparency, which align with the Sustainable Development Goals (SDGs). Second, in Thailand, despite challenges, existing regulations can support a balance between marketing innovation and sustainable consumer rights protection. Third, expanding regulations in Indonesia is also essential to improve consumer protection in the digital era. While endorsement practices on Instagram often lead to ethical violations, Indonesia does not yet have a specific policy regarding influencers. Therefore, increasing awareness and clear regulations will ensure more transparent, fair, and ethical marketing practices on social media platforms like Instagram.